Methotrexate-related lymphoproliferative disorder of the oral region in patients with rheumatoid arthritis. Issue 4 (July 2016) - Kondo, Keisuke; Nakamura, Satoshi; Takahashi, Masayuki; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract: Objective: The purpose of this study was to verify the characteristics of methotrexate (MTX)-related oral lymphoproliferative disorders (LPDs) in rheumatoid arthritis (RA) patients. Methods: Twenty-eight cases of MTX-related oral LPDs with RA, which included 14 cases from English articles and 14 cases from Japanese literature, were collected. Data on demographic characteristics, clinical features, pathological diagnosis, weekly and total amount of MTX, concomitant drugs for RA, treatment, and follow-up period and outcomes were analyzed. Results: Gingiva was the most frequent site (19, 67.9%), followed by tongue (4, 14.3%). Histopathologically, 15 cases (78.9%) were diffuse large B-cell lymphoma. All oral cases except for one case were Epstein–Barr virus (EBV)-positive. As an initial treatment, MTX was withdrawn for all cases including two cases of firstly decreasing the dose of MTX. Recurrence was reported in one case (4.8%). In gingival 19 cases, ulceration was found in 16 cases (84.2%), pain in 13 cases (68.4%) and alveolar bone exposure in 11 cases (57.9%). Conclusions: The occurrence of MTX-related oral LPDs showed a predilection for gingiva with frequent characteristics of ulceration, pain and bone exposure. Almost all cases were EBV-positive.